Quantitative ultrastructural characteristics of platelets in the patients with diabetes mellitus type 2 in a compensation with arterial hypertension under correction of arterial blood pressure with losartan - Pertseva N.O. (Морфологія, 2011)
We have conducted a quantitative evaluation of ultrastructural changes in the dynamics of platelets in the patients with diabetes mellitus type 2 in a compensation phase with arterial hypertension under correction of arterial blood pressure with losartan and with considering of microalbuminuria. It is show n that in the patients with normalbuminuria observed moderate degree violations of thrombocyte hemostasis , as a result of this is a significant in crease in the relative amount of activated plate-lets with preservation of normal content aggregated and degranul ated forms and the appearance of single platelets with an im-balance of alpha and delta granules. Losa rtan usage makes it possible to normalize u ltrastructural disorders of platelets ranging from the 6th month of the treatment. In the patients with microa lbuminuria showed a significant damage of thrombocyte hemos-tasis due to significant growth in the content of the activated, degranulated and aggregated form s of platelets and development of hyperactivation of platelets by hyaline type. The standard treatment for one year is accompanied by increasing imbalance of granulomer of most platelets and the degree of the heteromorphic pool with a significant increase in aggregate form. Inclusion of losartan in the treatment leads to a substantial reduction of pathomorphological ch anges of platelets, limitation of their hyperactivity and prevents the formation of giant spherical pseudopodial forms from the 6th month of starting treatment.